2019
DOI: 10.1016/s2213-8587(19)30001-4
|View full text |Cite
|
Sign up to set email alerts
|

Community groups or mobile phone messaging to prevent and control type 2 diabetes and intermediate hyperglycaemia in Bangladesh (DMagic): a cluster-randomised controlled trial

Abstract: Summary Background Strategies are needed to prevent and control type 2 diabetes and intermediate hyperglycaemia, which together affect roughly a third of adults in Bangladesh. We aimed to assess the effects of mHealth and community mobilisation on the prevalence of intermediate hyperglycaemia and diabetes among the general adult population in rural Bangladesh, and to assess the effect of these interventions on the incidence of type 2 diabetes among people with intermediate hyperglycae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(147 citation statements)
references
References 27 publications
1
146
0
Order By: Relevance
“…In a recent study in Bangladesh, a community-based intervention with facilitator-led group meetings was effective in preventing type 2 diabetes when an SMS-based intervention alone was not [36]. These studies and our own are compatible with the conclusions from a recent systematic review of electronically delivered weight loss programmes [37] that electronic delivery of lifestyle advice and motivation alone may be less effective than when supplemented with remote counselling or counselling in person.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent study in Bangladesh, a community-based intervention with facilitator-led group meetings was effective in preventing type 2 diabetes when an SMS-based intervention alone was not [36]. These studies and our own are compatible with the conclusions from a recent systematic review of electronically delivered weight loss programmes [37] that electronic delivery of lifestyle advice and motivation alone may be less effective than when supplemented with remote counselling or counselling in person.…”
Section: Discussionsupporting
confidence: 87%
“…Although prediabetes is commonly asymptomatic, it represents a window of opportunity to prevent progression to type 2 diabetes and its complications 33. Community mobilisation and lifestyle intervention for prediabetes can lead to a significant reduction in the incidence of diabetes 2934. Follow-up studies from the Diabetes Prevention Programme have shown that lifestyle intervention can be cost effective in preventing diabetes, and that treatment with metformin can even be cost saving 35.…”
Section: Discussionmentioning
confidence: 99%
“…There was no effect of mHealth on the combined prevalence of intermediate hyperglycaemia and diabetes, or the incidence of diabetes. 29 This paper reports on the pre-trial formative research to inform the development of PLA and mHealth interventions. We used a qualitative methodology to explore community and individual perceptions of diabetes and associated risk factors (including physical activity) with men and women with and without diabetes, and health workers, in rural Faridpur, in order to design contextually appropriate content and methods for the mHealth and PLA interventions.…”
Section: Gender and Behaviour Changementioning
confidence: 99%